2013
DOI: 10.1016/j.jpainsymman.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Use of Opioid Analgesics Among Older Persons With Colorectal Cancer in Two Health Districts With Palliative Care Programs

Abstract: Context-Prescription of opioid analgesics is a key component of pain management among persons with cancer at the end of life.Objectives-To use a population-based method to assess the use of opioid analgesics within the community among older persons with colorectal cancer (CRC) before death and determine factors associated with the use of opioid analgesics.Methods-Data were derived from a retrospective, linked administrative database study of all persons who were diagnosed with CRC between January 1, 2001 and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Similarly, studies focused exclusively on people aged above 65 years related to palliative pain care management are scarce and the available evidence-base lacks high-quality RCT findings. [40][41][42][43][44]…”
Section: Palliative and End Of Life Carementioning
confidence: 99%
“…Similarly, studies focused exclusively on people aged above 65 years related to palliative pain care management are scarce and the available evidence-base lacks high-quality RCT findings. [40][41][42][43][44]…”
Section: Palliative and End Of Life Carementioning
confidence: 99%
“…Palliative care use was associated with more frequent prescription of opioids in our univariable analysis. Wang et al, 22 Tse et al, 23 and Fisher et al, 24 reported older pancreatic cancer patients using palliative care consumed opioids significantly more frequently than those receiving standard oncology care. We suggest that the higher likelihood of using opioids among those with palliative care use might be attributed to the practice of prescribing strong and high dose opioids to manage severe pain for cancer patients in the palliative care stage 17,18 …”
Section: Discussionmentioning
confidence: 99%
“…In order to fill this knowledge gap, many developed countries calculate the total amount of opioids prescribed to cancer patients by analyzing administrative claims data or prescription database (3)(4)(5). Claims data are useful for monitoring medical utilization and prescription patterns, but it requires that its accuracy, validity and reliability are tested, so that characteristics and limitations of the dataset is well understood by those who use the data for future research (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%